MCLL Handbook - McGill Community For Lifelong Learning (MCLL) (2013)

The Newsletter : Fall 2018: Volume 29, No. 3 - McGill Community For Lifelong Learning (MCLL) (2018)
Number of pages: 12

The Newsletter : Spring 2019: Volume 30, No. 2 - McGill Community For Lifelong Learning (MCLL) (2019)
Number of pages: 8

The Newsletter : Winter 2019: Volume 30, No. 1 - McGill Community For Lifelong Learning (MCLL) (2019)
Number of pages: 12

Moderators’ Handbook : September 2019 - McGill Community For Lifelong Learning (MCLL) (2019)

Report of the Planning Committee on the 2018 Members’ Forum - McGill Community For Lifelong Learning (MCLL) (2018)
A Members’ Forum was held on 26 October 2018 to discuss the issue of peer learning at MCLL. The three major findings and the four recommendations are presented here

McGill Community for Lifelong Learning : Elected Council Members and Committee Chairs - McGill Community For Lifelong Learning (MCLL) (2019)